Effect of quarter circle ribs radius and its location in a suddenly expanded flow at sonic Mach number - Khan, Ambareen; Ghasi Mahaboobali, Fharukh Ahmed; Zuraidi, Nur Husnina Muhamad; Khan, Sher Afghan; Sapardi, Mohd. Azan Mohammad; Pathan, Khizar Ahmed; Shaikh, Javed Shoukat (Semarak Ilmu Publishing, 2025)
A sudden increase in area and flow expansion is typical in the automotive and defence industries. The flow becomes divided at the base, creating low-pressure recirculation at the blunt base of the fuselage, missiles, projectiles, and aircraft bombs, which causes the base drag to increase noticeably. This paper addresses how this low base pressure at the base can be controlled. This investigation aims to maintain the separated recirculation flow via a passive control technique, such as quarter-circle ribs, where the shape varies with the variation in the rib radius. The impact of ribs on the base flow as a passive flow control mechanism on base pressure at critical Mach number is explored. Quarter-circular-shaped ribs manage the flow field into an abruptly enlarged duct from the sonic nozzle. Several variables were examined in the study, including the effects of rib orientations, rib placements, rib diameters, duct lengths, and rib locations. The ribs are arranged around the circumference of the duct. The flow from the converging nozzle at the sonic Mach number expands suddenly. Numerical research was conducted on ribs at various foundation wall positions. The area ratio is 6.25, and the rib radii considered are 1 to 5 mm, in increments of 1 mm. The NPR ranges that are simulated are 1.5 to 5. As per the results, a taller rib with a higher NPR tends to increase base pressure, while a smaller rib with a lower NPR effectively decreases base pressure. The simulation was performed on a duct with a 25 mm diameter, where the NPRs were both over- and under-expanded. Here, the ribs range in radius from 3 mm to 5 mm and have an aspect ratio of 1. They raise the NPR from 1.5 to 5 and are placed at 0.5, 1 D, 1.5 D, 2 D, and 3 D from the foundation wall. The results suggest that the position and size of the ribs may also play a considerable part in regulating the base pressure